2008
DOI: 10.1007/s10494-008-9171-1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Diesel Spray Evaporation in a “Stabilized Cool Flame” Reactor: A Comparative Study

Abstract: The major objective of this work is to numerically investigate the interacting physical and chemical phenomena that characterize the flow in a stabilized cool flame diesel fuel spray evaporation system. A two-phase RANS computational fluid dynamics code has been developed and used to predict the characteristics of the developing turbulent, multiphase, multi-component, reactive flow-field. The code employs a Eulerian-Lagrangian approach, taking into account the mass, momentum, thermal and turbulent energy excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…The relatively large heat losses caused by turbulence in the other regions of the flow field tend to increase the autoignition delay time, since the rate of heat production by the chemical reaction is slower than the rate of heat loss. When heat losses at the system boundaries are completely balanced by heat generation resulting from the exothermal chemical reactions, such steady-state thermochemical conditions do not result in autoignition (Kolaitis and Founti, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The relatively large heat losses caused by turbulence in the other regions of the flow field tend to increase the autoignition delay time, since the rate of heat production by the chemical reaction is slower than the rate of heat loss. When heat losses at the system boundaries are completely balanced by heat generation resulting from the exothermal chemical reactions, such steady-state thermochemical conditions do not result in autoignition (Kolaitis and Founti, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that, contrary to "conventional" non-premixed combustion technical devices, where chemical reactions occur mainly in a distinct "thin" flame zone, cool flame reactivity zones are "thick" and cover a significant part of the device's volume. In this context, numerical simulations, presented in a recent publication [32] attempting to classify SCF on the basis of characteristic time scales, revealed that the developing thermo-chemical conditions exhibit mainly characteristics of the "distributed reaction zones" regime.…”
Section: Multi-component Reactive Flow-fieldmentioning
confidence: 99%
“…Aiming to validate the developed computational approach, predictions are compared with available temperature measurements (c.f. Figure 1), obtained in the SCF reactor [32], for the three considered Test Cases. In Figure 11, temperature predictions along the reactor's symmetry axis are compared with the experimental data.…”
Section: Model Validationmentioning
confidence: 99%
“…Не дивлячись на підвищену точність розрахунку турбулентних потоків LES вимагає значні обчислювальні потужності. Оскільки в даному дослідженні цікавить прикладна сторона процесу випаровування, а саме теплогідродинамічна задача утворення парогазової суміші та її теплотехнічні характеристики, отримання усереднених по часу полів швидкостей за допомогою RANS із суттєвою економією обчислювальних ресурсів [7] визначає подальше застосування його в якості моделі турбулентності та k-ε моделі обчислення в'язкості вихору.…”
unclassified